Role play: let's act it out! / Anis Idayu Aziz ...[et al.] - Aziz, Anis Idayu; Raja Yacob, Raja Nur Hidayah; Suhaimin, Mohd Faiez; Wan Ismail, Wan Saiful 'Azzam; Abd Razak, Amanina (Universiti Teknologi MARA, 2018)
Generally, most university students are reluctant to speak English in public due to lack of Englishproficiency. This situation has led to lost interest in role-play activity among UiTM Cawangan Kelantan students; particularly Integrated Language Skills 1 (ELC121) students. Hence, this project intends to increase students' interest in role-play activity as well as enhance students' proficiency in English language especially in role-play assessment. This project focuses on using Interactive DVD as a tool tohelp in motivating the student's interest and enhancing student's proficiency level. This interactive DVD iscomprised of notes, samples of dialogues and video presentations meant for teaching and learning role- play. Based on the outcomes, the students show positive enthusiasms in joining the class and perform outstandingly in role-play test. The Interactive DVD motivates them to actively participate in role play activity with confidence.